SOSIALISASI PENDIDIKAN PRA NIKAH BERBASIS NILAI KEISLAMAN DI DESA LAWEYAN PROBOLINGGO - Ika Widia Ningsih; Fatimatus Zahro; Siti Nurhaliza S.R; M. Jadid Khadavi; Irma Mila Karimah (JURNAL ILMIAH NUSANTARA, 2025)
Marriage is a crucial phase in human life that requires preparation not only administratively but also mentally, spiritually, and socially. A lack of understanding regarding marital rights and obligations, communication, and conflict management often becomes a key factor leading to family conflicts and divorce, particularly among young couples. This article discusses the implementation of premarital education based on Islamic values in Laweyan Village, Sumberasih District, Probolinggo Regency, carried out through the NGOPRAH program (an acronym for Ngopi dan Ngobrol bareng tentang Pra Nikah or “Coffee and Talk about Premarital Issues”). This Community Service (PkM) activity was conducted on August 15, 2025, involving 29 participants consisting of youth, prospective brides and grooms, parents, and community leaders. The main speaker was from the Indonesian Child Protection Commission (KPAI) of Probolinggo Regency, delivering material on marriage readiness, child protection, and the prevention of early marriage. The study applied a Participatory Action Research (PAR) approach, with data collected through participatory observation, interviews, focus group discussions, and documentation. The results indicated a significant increase in participants’ understanding of Islamic values in marriage, including spousal rights and obligations, effective communication, and readiness to build harmonious families (sakinah, mawaddah, wa rahmah). Evaluation revealed that 85% of participants gained new insights into the importance of premarital preparation. Therefore, the NGOPRAH program can serve as an alternative model of premarital education based on Islamic values, with potential for replication in other communities.